PENDEKATAN EPISTEMOLOGI DAN INTERSUBJEKTIF ATAS HADIS-HADIS NIKAH MUT’AH - Haqqi, Muhammad Nashrul (Al-Ahkam, 2014)
This article offers an alternative perspective at the difference views in the Sunni and Shi’ite hadiths for Mut'ah marriage. Related to the differences both treat and apply that these hadits universally believed to be one of the fundamental sources of Islam. Eventhough, both Sunny and Shi’ite agree to put hadits as a second source of doctrine, but they often actually produce a different formulation of the law and contradictory. The difference of theological view is a fundamental problem that implies on their thought dealing with being accepted or rejected for hadits transmition of Mut’ah merriage. Intersubjectivity approach has roled to positionize these groups as an objective opinion, subjective as well. Both objectivities are located on the seriousness of their respective efforts to obtain the authenticity of the hadith, in which expectations will be both objectivity when hadith of mut’ah marriages take placed purely as historical information. In this position, the awareness together to build the Islamic civilization in the theological differences, are values that should be a priority